The Head and Neck Cancer Cell Oncogenome: A Platform for the Development of Precision Molecular Therapies - Martin, Daniel (2014)
The recent elucidation of the genomic landscape of head and neck squamous cell carcinoma (HNSCC) has provided a unique opportunity to develop selective cancer treatment options. These efforts will require the establishment of relevant HNSCC models for preclinical testing. Here, we performed full exome and transcriptome sequencing of a large panel of HNSCC-derived cells from different anatomical locations and human papillomavirus (HPV) infection status. These cells exhibit typical mutations in TP53, FAT1, CDK2NA, CASP8, and NOTCH1, and copy number variations (CNVs) and mutations in PIK3CA, HRAS, and PTEN that reflect the widespread activation of the PI3K-mTOR pathway. SMAD4 alterations were observed that may explain the decreased tumor suppressive effect of TGF-β in HNSCC. Surprisingly, we identified HPV+ HNSCC cells harboring TP53 mutations, and documented aberrant TP53 expression in a subset of HPV+ HNSCC cases. This analysis also revealed that most HNSCC cells harbor multiple mutations and CNVs in epigenetic modifiers (e.g., EP300, CREBP, MLL1, MLL2, MLL3, KDM6A, and KDM6B) that may contribute to HNSCC initiation and progression. These genetically-defined experimental HNSCC cellular systems, together with the identification of novel actionable molecular targets, may now facilitate the pre-clinical evaluation of emerging therapeutic agents in tumors exhibiting each precise genomic alteration.